DETERMINANT FACTORS RELATED TO THE WORK MOTIVATION OF EXECUTIVE NURSES AT YARSI HOSPITAL JAKARTA - Hasanah, Siti (Rifapublisher.id, 2024)
Background: Motivation is a drive that stimulates employees to seek and achieve satisfaction in their work. A balance of intrinsic and extrinsic motivation leads to greater job satisfaction and will enhance performance. Objective: This study aims to determine the relationship between gender, age, education, work experience, marital status, compensation, coaching, and supervision with the work motivation of executive nurses at YARSI Hospital Jakarta. Method: This research uses a quantitative method with an analytical survey and a cross-sectional approach. The number of respondents in this study was 130 executive nurses in outpatient and inpatient wards. Bivariate data analysis used chi-square and logistic regression for multivariate analysis. Result: Relationship between compensation and work motivation, with a p-value of 0.001<0.05. Relationship between coaching and work motivation, with a p-value of 0.014 < 0.05. There is no relationship between supervision and work motivation. Multivariate analysis results showed that the education variable has an OR value of 0.447, higher than coaching and compensation. Conclusion: The conclusion of the study indicates that coaching, compensation, and education are variables related to work motivation, with education being the most influential variable in increasing work motivation.